MENINGKATKAN SERVIS BAWAH BOLA VOLI MELALUI METODE TAHAPAN DI SDN 09 SEMADU - David, Ginseng (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study was to determine the stage of an improved method for learning outcomes on student services under SDN 09 Semadu Sekadau. Forms of research is classroom action research. Subjects were teachers collaborate with fourth grade students of SDN 09 Semadu Sekadau as many as 28 students. Based on the results of this study concluded that there is an increase in the results of the first cycle of completeness by the same percentage that the number of 14 students or 50%, and students who have not completed totaled 14 students or 50%. While the second cycle there is a category of student outcomes to complete all of the graduating students numbered 28 students or equal to 100% and unresolved amounted to 0 or does not exist. Keywords: Servis Down, Methods Stages